2022
DOI: 10.1158/0008-5472.can-21-2116
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of Prostaglandin E2 Signaling in Cancer-Associated Fibroblasts Limits Mammary Carcinoma Growth but Promotes Metastasis

Abstract: The activation and differentiation of cancer-associated fibroblasts (CAF) are involved in tumor progression. Here, we show that the tumor-promoting lipid mediator prostaglandin E2 (PGE2) plays a paradoxical role in CAF activation and tumor progression. Restricting PGE2 signaling via knockout of microsomal prostaglandin E synthase-1 (mPGES-1) in PyMT mice or of the prostanoid E receptor 3 (EP3) in CAFs stunted mammary carcinoma growth associated with strong CAF proliferation. CAF proliferation upon EP3 inhibiti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 54 publications
0
12
0
Order By: Relevance
“…PGE-MUM is a urinary metabolite of PGE2 and represents the activity of the COX-2 pathway. COX-2 and COX-2-derived PGE2 are reportedly involved in the tumour initiation and proliferation of cancer cells both in vitro and in vivo [ 5 , 16 ]. Several studies performed in clinical settings have shown that COX-2 overexpression is associated with poor prognosis in solid tumours, including NSCLC [ 6 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PGE-MUM is a urinary metabolite of PGE2 and represents the activity of the COX-2 pathway. COX-2 and COX-2-derived PGE2 are reportedly involved in the tumour initiation and proliferation of cancer cells both in vitro and in vivo [ 5 , 16 ]. Several studies performed in clinical settings have shown that COX-2 overexpression is associated with poor prognosis in solid tumours, including NSCLC [ 6 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since the lungs play an important role in both the production and metabolism of PGE2, PGE2 levels in clinical specimens are possible indicators of inflammation-associated lung disorders [ 4 ]. Furthermore, COX-2-derived PGE2 is reportedly the most significant prostaglandin involved in cancer progression [ 3 , 5 ]. Although previous studies investigating the association between COX-2/PGE2 activity in tumour tissue and tumour progression have been conducted, accurately measuring its expression in tissue samples has several limitations, such as its rapid degradation, invasiveness of sampling and tumour heterogeneity [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…For lung cancer, it has been shown that CAY10526 restores T-cell immunity via inhibition of mPGES1, contributing to suppression of lung metastasis in Gprc5a-ko mouse model (17). In breast cancer, disruption of PGE2 signaling in CAFs represses carcinoma growth but promotes metastasis (30). Another study support the prognostic value of mPGES1, and suggest targeting this pathway may serve as novel therapeutic avenue for melanoma (22).…”
Section: Abnormal Activation Of Specific Jak/stat Signal Results Inmentioning
confidence: 86%
“…In our group, we reported that c-Jun N-terminal kinase served a role in the mPGES-1/PGE2/EP4/MAPK positive feedback loops in T-ALL cells. Meanwhile, P38 and extracellular signal-regulated kinase 1/2 exerted negative feedback on mPGES-1 (5,30). More recently, we published that mPGES-1/PGE2 promoted proliferation of T-ALL cells by modulating MTDH via the EP3/cAMP/ PKA/CREB pathway (7).…”
Section: Abnormal Activation Of Specific Jak/stat Signal Results Inmentioning
confidence: 99%
See 1 more Smart Citation